PERANCANGAN APLIKASI MONITORING SERVIS PRINTER PADA FB PRINTER BERBASIS WEBSITE - Barreta, Ellank; Listyorini, Tri; Supriyati, Endang (Teknika, 2024)
FB Printer is a printer service that experiences various problems in the manual monitoring and recording system. These problems often cause data loss or damage and difficulties in the recording process, ultimately reducing efficiency and customer satisfaction. This study aims to develop a web-based monitoring system that is able to monitor printer repairs in real time, improve data recording efficiency, and increase customer satisfaction by providing notifications via WhatsApp and email. This system uses the waterfall method to provide more efficient and accurate data recording and allows customers to see the status of printer repairs easily. In addition, customers will also receive payment reports via midtrans, which simplifies the payment process. This system also offers a 10% discount after customers have had 10 services as a form of appreciation for customer loyalty. The results of the study show that this system is not only able to provide efficient repair data recording but also increases accessibility and overall customer satisfaction. Hopefully, this system can provide convenience, efficiency, and accessibility, which are important for the smooth operation of FB Printer's printer services, thereby creating a better customer experience and increasing company productivity.